Coping trajectory of social isolation in individuals with maintenance haemodialysis: A descriptive qualitative study - Jie Zou; Jiao Xie; Jinyong Zhang; Hangdi Zhao; Pingjing Lu (Elsevier, 2024)
Background: : The number of individuals undergoing maintenance haemodialysis has continued to increase in recent years. This treatment method can lead to social isolation, which has a significant impact on an individual's health. Unfortunately, research on this issue is insufficient, and no effective interventions have been developed. Moreover, existing research lacks attention to and understanding of patient aspirations-a critical area that warrants further exploration. Objectives: : We aimed to reveal the natural coping trajectory of individuals undergoing maintenance haemodialysis in the context of social isolation to provide a useful reference for further research and the development of effective interventions. Design: : This was a descriptive qualitative study. Setting (s): This study was conducted at a haemodialysis centre in a provincial capital city of northern China. Participants: Using maximum variant and purposive sampling, we recruited 15 patients undergoing maintenance haemodialysis. Methods: : The interviews were transcribed verbatim, and data were analysed using deductive content analysis. Results: Three themes were identified: (a) prerequisites for coping with social isolation; (b) maintaining the bond between coping and social isolation; and (c) the results of coping with social isolation. These themes revealed the natural trajectory of individuals undergoing maintenance haemodialysis in dealing with social isolation. Conclusion: : We interpreted the findings to mean that it was necessary to establish a three-way linkage among family, hospitals, and society to develop multicomponent and multilevel intervention measures. Tweetable abstract: : A study of the response of individuals undergoing maintenance haemodialysis to social isolation revealed their coping trajectory and conveyed their aspirations.